Quality education and gender equality as objectives of sustainable development in education: an experi-ence with teachers in Spain - Juan López-Morales; Mayra Urrea-Solano; Olalla García-Taibo; Salvador Baena-Morales (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This paper aims to assess the opinions of Physical Education teachers (PET) about their teaching intervention at a coeducational level. A further objective was to analyse PETs self-perceptions of their mixed and training interventions to describe possible training gaps. The qualitative study involved 191 high school PET from Andalusia (Spain). Some questions were conducted about three dimensions: gender stereotypes and attitudes in PE; teaching performance in coeducation, and coeducational teachers’ professional development in PE. The study's main results indicated that most teachers had neither different expectations of boys and girls nor a different way of treating them and, more than half of the participants considered themselves to be competent in coeducation. They preferred to receive training other than coeducational training. However, almost three-quarters of the sample had not received any coeducation training, or it was self-taught. The main conclusion is that PET consider that they have proper coeducational behaviour. The results showed that current teachers had improved their teaching intervention regarding gender equality compared to previous studies. The present study has had a contribution to the Sustainable Development Goals (SDG )goals 4 and 5, quality education and gender equality, respectively and can be a reference for future research related to coeducation for teachers.